2014
DOI: 10.2108/zs130271
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Population Histories of the Deep-Sea Demersal Fish, Lycodes matsubarai, in the Sea of Japan and the Sea of Okhotsk

Abstract: Recent studies have revealed the impact of the drastic climate change during the last glacial period on coastal marine and anadromous species in the marginal seas of the northwestern Pacific Ocean; however, its influence on deep-sea species remains poorly understood. To compare the effects of the last glacial period on populations from the Sea of Japan and the Sea of Okhotsk, we examined the mitochondrial control region and cytochrome b gene sequences of Lycodes matsubarai, a deepsea demersal fish that inhabit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…During the LGM, the Sea of Japan was almost completely isolated from neighboring seas, the bottom of the former becoming anoxic due to significant freshwater input into the surface water layer (Oba et al 1991;Tada et al 1999;Tyler 2002). Some authors suggested that such environmental changes resulted in significant population size reductions of deep-sea demersal fishes, and subsequently sudden population size expansions might have occurred after the LGM (e.g., Shirai et al 2006;Sakuma et al 2014). Similarly, the mismatch distribution well fitted the theoretically expected curve under the sudden expansion model and the significant departures from the equilibrium also suggested a sudden expansion of the historical population size of SJ C. matsushimae ( Fig.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…During the LGM, the Sea of Japan was almost completely isolated from neighboring seas, the bottom of the former becoming anoxic due to significant freshwater input into the surface water layer (Oba et al 1991;Tada et al 1999;Tyler 2002). Some authors suggested that such environmental changes resulted in significant population size reductions of deep-sea demersal fishes, and subsequently sudden population size expansions might have occurred after the LGM (e.g., Shirai et al 2006;Sakuma et al 2014). Similarly, the mismatch distribution well fitted the theoretically expected curve under the sudden expansion model and the significant departures from the equilibrium also suggested a sudden expansion of the historical population size of SJ C. matsushimae ( Fig.…”
Section: Discussionmentioning
confidence: 58%
“…In studies of other demersal fishes in the Sea of Okhotsk, a dramatic change in population size has been demonstrated in the lumpsucker Eumicrotremus asperrimus (see Kai et al 2015). Furthermore, Sakuma et al (2014) revealed that the population size of Lycodes matsubarai in the Sea of Okhotsk had been stable for most of the last 40,000 years, suddenly reducing in the last few hundred years. Conversely, Kodama et al (2008) found no evidence of sudden Table 1 A.…”
Section: Discussionmentioning
confidence: 99%
“…Lycodes matsubarai indicated the high genetic population structure because they have been restricted post-glacial migration between western coast of Japan and Sea of Okhotsk by the shallow strait (13–55 m depth) (Sakuma et al. 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, E. burgeri in Kyoto might have experienced extinction and recolonization in anoxic bottom condition during glacial and interglacial cycle. Some deep-sea species might have experienced a rapid decrease in anaerobic or hypoxia environment after the western coast of Japan was separated from Pacific Ocean during the LGM, which might have influenced their low genetic diversity (Adachi et al 2009;Sakuma et al 2014;Habib et al 2015).…”
Section: Sequence Variation and Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation